REDUCTION OF FOOD COSTS AND WASTE IN PRE-PREPARATION OF MEALS BY IMPLEMENTING TECHNICAL TOKENS IN A FORTALEZA-CEARÁ FOOD AND NUTRITION UNIT - Dayseane Rocha Alves, Maria; Soares Damasceno, Leandro; Freitas Simôes, Eliziane; Guillen Pumar, Nayara; Cavalcante Carvalho Campos, Natália; de Paes Borges Herculano, Rosiane; Suênia Silva de Sousa, Verlaine; Nogueira de Queiróz Almeida, Rosane; Oliveira Pimentel, Luciana; Gorete Lotif Lira, Maria (Health and Society, 2024)
The Food and Nutrition (HFS) is a unit which develops activities related to food and nutrition, providing safe meals. To reduce waste, it can be used to produce sheet (FTP) that it is an effective tool for the control of production of foodstuffs both in financial as well as nutrition. This work aims to standardize and reduce waste in the pre-preparation and cost of preparations by deploying factsheets on a Power Unit Nutrition business in Fortaleza-Ceará. This is an observational study, prospective, descriptive quantitative, with six days of execution. The fact sheets were made of five (5) dishes present in the unit in which menu was composed of entrance, main dishes, base plate, trim and desserts. Among the FC obtained in this study there was a significant variation in the results available in the literature, making it possible to compare the losses, evaluation of raw materials, storage, receipt and hand labor used. With the reduction of factors, therefore there was a reduction in the cost of the preparation of the meals, as FC interfere with cost values, the sales price is an important factor in determining the profit of the company. Based on the data presented, it is concluded that this data sheet is a very important tool for the units of food and nutrition, it provides a reduction in waste and cost of preparations, and contribute to the choice of supplier, upon receipt, storage , handling, assisting in the planning of purchasing, control production costs and providing a standard and quality of meals.